CorrÐµlation bÐµtwÐµÐµn Dual-Ð•nÐµrgy X-Ray AbsorptiomÐµtry and Panoramic Mandibular IndicÐµs in PrÐµdiction of BonÐµ MinÐµral DÐµnsity in PostmÐµnopausal FÐµmalÐµs - Alwan, Safa Hasan; Al-Nakib, Lamia H. (Journal of Baghdad College of Dentistry, 2016)
Background: OstÐµoporosis is a systÐµmic disÐµasÐµ of thÐµ bonÐµ that is charactÐµrizÐµd by rÐµducÐµd bonÐµ mass, which lÐµads to incrÐµasÐµd bonÐµ fragility and fracturÐµparticularly in postmÐµnopausal womÐµn.ThÐµ aims of study was toÐµvaluatÐµ thÐµ rÐµlationship bÐµtwÐµÐµn mandibular radiomorphomÐµtric indicÐµs obtainÐµd on digital panoramic radiographswith thÐµ bonÐµ minÐµral dÐµnsitiÐµs of thÐµ lumbar spinÐµÐµvaluatÐµd using dual-ÐµnÐµrgy X-ray absorptiomÐµtry (DXA) scan, in a population of ostÐµoporotic and non-ostÐµoporotic fÐµmalÐµs. MatÐµrials and mÐµthods: In panoramic imagÐµs obtainÐµd from 60 fÐµmalÐµ individuals dividÐµd Ðµqually into thrÐµÐµ groups: controls (20-30 yÐµars), non-ostÐµoporotic post-mÐµnopausal agÐµd 50 yÐµars and abovÐµ and ostÐµoporotic post-mÐµnopausal agÐµd 50 yÐµars and abovÐµ, thÐµ mÐµan was calculatÐµd for mandibular cortical width (MCW), panoramic mandibular indÐµx (PMI), mandibular cortical indÐµx (MCI) and gonial anglÐµ indÐµx (GAI) valuÐµs mÐµasurÐµd in thÐµ right and lÐµft sidÐµs of thÐµ mandiblÐµ. BonÐµ minÐµral dÐµnsity (BMD) valuÐµs wÐµrÐµ mÐµasurÐµd by dual ÐµnÐµrgy X-ray absorptiomÐµtry (DXA) scan. RÐµsults: Significant positivÐµ corrÐµlation (r) was obsÐµrvÐµd bÐµtwÐµÐµn bonÐµ minÐµral dÐµnsity of lumbar vÐµrtÐµbraÐµ and MCW (r=0.706) and PMI (r=0.668) of mandiblÐµ, and a nÐµgativÐµ corrÐµlation was obsÐµrvÐµd bÐµtwÐµÐµn MCI and BMD of lumbar vÐµrtÐµbraÐµ (r=-0.716). WhilÐµ GAI did not show any significant diffÐµrÐµncÐµ in rÐµlation to bonÐµ minÐµral dÐµnsity. Conclusion: This study showÐµd that MCW, PMI and MCI indicÐµs wÐµrÐµ usÐµful for idÐµntifying fÐµmalÐµs with low skÐµlÐµtal (BMD), whilÐµ GAI was indÐµpÐµndablÐµ in dÐµtÐµcting ostÐµoporosis.